Forma organizacyjno-prawna a gospodarka finansowa szpitala - Rój, Justyna (Legal Form and Organizational Aspects and Hospital Finance Management, 2006)
The paper is a voice in discussion regarding to the legal form of hospital activity. The definition of hospital and criteria of choosing the proper legal form for hospital were presented and particularly the possibility of using variety of financing sources. The change of legal form of hospital activity is conductive to the higher rationality of hospital finance, increase of different financing sources availability, efficiency of hospital performance. This change would have impact on the improvement of services quality, which has influence on patients satisfaction. So those are the main reasons to convert hospital in Poland into joint stock company with simultaneous increasing of private capital. Increasing availability of different financing sources would ensure the increase of hospital investment activity. In the article, it was underlined that those changes in legal form of hospital should be accompanied by changes in regulation and financing at the heath care system level which ensured that the goal of it will be realized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 53-57